The importance of housing, neighborhood and community contexts - Allison, K.W.; Broce, R.S.; Houston, A.J. (Adolescent Development and School Achievement in Urban Communities: Resil. in the Neighborhood, 2012)
Keywords: dept.swk

Revitalizing the vision in supervision: supporting the supervisor in home-based therapy programs - Rodriguez-Keyes, Elizabeth; Gossart-Walker, Sandy; Rowland, Cecilia (Smith College Studies in Social Work, 2012)
Home-based programs provide a growing number of mental health and case-management services to high-risk children, adolescents, and their families. The clinical service providers who work directly with these children and families have varying degrees of education and practice experience as well as a range of different supervisory needs. Because of the daily challenges service providers face, they require support from competent, available supervisors. The professionals who supervise them often assume that responsibility with limited, if any, training in providing supervision. New and experienced supervisors alike often find themselves in positions for which they are ill prepared, without suitable training or administrative support. This article describes a supervision seminar developed for supervisors who supervise the clinicians who provide home-based services. The seminar provides training, support, consultation, and other forms of assistance to help supervisors adapt their clinical skills for use in their supervisory roles.
Keywords: clinical supervision; clinical supervisor; dept.swk; home-based therapy; supervision seminar

The miracle bearers: narratives of birthing women and implications for spiritually informed social work practice - Schneider, Dana A (Journal of Social Service Research, 2012)
Women's childbirth experiences are not widely researched in the social work literature. Therefore, the purpose of this study is to answer questions related to the child-birthing experience. One hundred and nineteen participants responded to a 26-item online questionnaire between April and June 2008, and their written narratives were analyzed using a grounded theory approach. Themes regarding the spiritual dimensions of childbirth emerged from the data and support current research demonstrating the importance of spirituality in women's lives and the meaningful and transformative nature of childbirth experiences. Implications for addressing spirituality in practice when working with childbearing women are explored. Future research that explores how spirituality may function as a protective factor for women with difficult pregnancies, births, and transitions to parenting is recommended.
Keywords: Childbirth; dept.swk; narratives; spirituality; transformation; women